Responding to protracted displacement using the Humanitarian-Development-Peace nexus approach: Scoping study - Rebecca Roberts (United Nations Research Institute for Social Development (UNRISD), 2020)
This scoping study has been commissioned by the United Nations Development Programme (UNDP) and the United Nations High Commissioner for Refugees (UNHCR) to inform the development of a Theory of Change (ToC; UNRISD 2020) that illustrates the potential for their interventions, based on the Humanitarian-Development-Peace (HDP) nexus, to work toward longer-term solutions and to reinforce, strategic collaboration in situations of forced displacement in low- and middle-income countries. Contexts vary so target populations might, for example, include refugees and asylum seekers, internally displaced persons (IDPs), returnees and stateless persons alongside host populations. The study was conducted by the United Nations Research Institute for Sustainable Development (UNRISD) between March and June 2020 and is based on a desk review and remote individual or group discussions with 50 people from UNDP, UNHCR and the Organisation for Economic Co-operation and Development (OECD).
Keywords: 330